PERSEPSI MENGENAI LINGKUNGAN KERJA TERHADAP PILIHAN KARIER SEBAGAI AUDITOR - Satrio, Arif Budi (MABIS, 2012)
The purpose of this research is to investigate the perceptions of accounting students about auditorâs work environment. This research is to examine and analyze auditorâs work environment affect opinion, work at accounting profession, and career plan of accounting students. The research was conducted with a purposive sampling technique in data collection. The research sample is determined by purposive sampling with criterion that is, the students of accounting department who still or finishing taking audit studying objects at Pontianak. The data collected is classified as primer data which obtained by questionnaires distribution. Testing hypothesis is conducted by using simple regression and multiple regressions. This research includes three of hypotheses. From three of hypothesis, two of hypotheses are rejected. The result of testing this hypothesis suggests that the work environment has a significance value of 0.029 which means it has a significant influence on student career choice for the auditor. This research is supports previous research conducted by Rasmini.